2003
DOI: 10.1016/s0896-6273(03)00126-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic or Pharmacological Iron Chelation Prevents MPTP-Induced Neurotoxicity In Vivo

Abstract: Studies on postmortem brains from Parkinson's patients reveal elevated iron in the substantia nigra (SN). Selective cell death in this brain region is associated with oxidative stress, which may be exacerbated by the presence of excess iron. Whether iron plays a causative role in cell death, however, is controversial. Here, we explore the effects of iron chelation via either transgenic expression of the iron binding protein ferritin or oral administration of the bioavailable metal chelator clioquinol (CQ) on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
455
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(481 citation statements)
references
References 79 publications
20
455
3
3
Order By: Relevance
“…These results suggest that alterations in ferritin H expression may directly contribute to the altered iron metabolism and increased oxidative stress present during the disease progression of PD. In fact, it was reported that overexpression of ferritin H prior to MPTP exposure in a mouse model of PD conferred resistance to the neurotoxic insult [20]. This seems to be consistent with the present study showing that ferritin H knockdown resulted in an increased percentage apoptotic cells following rotenone treatment (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results suggest that alterations in ferritin H expression may directly contribute to the altered iron metabolism and increased oxidative stress present during the disease progression of PD. In fact, it was reported that overexpression of ferritin H prior to MPTP exposure in a mouse model of PD conferred resistance to the neurotoxic insult [20]. This seems to be consistent with the present study showing that ferritin H knockdown resulted in an increased percentage apoptotic cells following rotenone treatment (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…A large body of evidence indicates a correlation between increased oxidative stress and the incidence of Parkinson's disease (PD) [4,19]. Recent studies have shown that iron chelators can block 6-hydroxydopamine and 1-methyl-4-phenyl-1,2,3,6-tetrapyridine (MPTP) induced dopaminergic cell death [20]. Excess free iron may be the catalyst in the production of deleterious ROS that are responsible for damage to DNA, lipids, and proteins, ultimately leading to the deletion of dopaminergic neurons [21].…”
Section: Introductionmentioning
confidence: 99%
“…Both extracellular and intracellular events related to ROS generation have a great impact on the fate of neurons. Suggested by the successful reports of metal chelation therapy for improving neuronal function and cell viability, redox-active iron is an attractive target for treatment of neurodegenerative disease [81,82]. Further investigation of iron will more clearly define the role of this redox-active element in the pathophysiology of AD.…”
Section: Resultsmentioning
confidence: 99%
“…Although it was initially considered a chelator [198][199][200][201], it has more recently been characterized as a copper/zinc ionophore, which functions to redistribute these metals into cells [196,[202][203][204][205][206]. Clioquinol is still considered a moderate iron chelator as it has been shown to lower iron levels in animal models of iron overload [64,148,[207][208][209][210], and has not been shown to redistribute iron into cells using ionophore assays.…”
Section: Clioquinol and Pbt2mentioning
confidence: 99%